2007
DOI: 10.1007/s00442-007-0871-3
|View full text |Cite
|
Sign up to set email alerts
|

Density-dependent resistance of the gypsy moth Lymantria dispar to its nucleopolyhedrovirus, and the consequences for population dynamics

Abstract: The processes controlling disease resistance can strongly influence the population dynamics of insect outbreaks. Evidence that disease resistance is density-dependent is accumulating, but the exact form of this relationship is highly variable from species to species. It has been hypothesized that insects experiencing high population densities might allocate more energy to disease resistance than those at lower densities, because they are more likely to encounter density-dependent pathogens. In contrast, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 30 publications
0
37
0
Order By: Relevance
“…However, animals did not show general depression of their immune system either in the social or the solitary context (in each case, one branch of the immune system was upregulated and the other downregulated), as would be expected if 'stress' were the cause (Reilly & Hajek 2008). Similarly, although workers in social groups compete for reproductive dominance (Honk et al 1981), this is unlikely to lead to similar immune changes in dominant and subordinate animals (Sapolsky 2004), and because our samples were taken at random with respect to dominance from the social groups it is unlikely to be an explanation for our results.…”
Section: Discussionmentioning
confidence: 93%
“…However, animals did not show general depression of their immune system either in the social or the solitary context (in each case, one branch of the immune system was upregulated and the other downregulated), as would be expected if 'stress' were the cause (Reilly & Hajek 2008). Similarly, although workers in social groups compete for reproductive dominance (Honk et al 1981), this is unlikely to lead to similar immune changes in dominant and subordinate animals (Sapolsky 2004), and because our samples were taken at random with respect to dominance from the social groups it is unlikely to be an explanation for our results.…”
Section: Discussionmentioning
confidence: 93%
“…An alternative hypothesis to density-dependent prophylaxis is the 'crowding and stress' hypothesis, which predicts that individuals reared at lower population densities will be in better physical condition, and hence will be better able to resist the negative effects of parasitism ( Goulson & Cory, 1995;Adamo, 2006;Reilly & Hajek, 2008 ). This idea is based on the assumption that increased stress and intra-specific competition will make hosts more susceptible to infection, or less able to tolerate the negative consequences of parasitism.…”
Section: Discussionmentioning
confidence: 99%
“…In insects, this hypothesis was initially examined by Steinhaus (1958) in studies of caterpillars and their natural pathogens. More recent experimental studies on lepidopteran hosts have shown that animals reared at higher densities experience reduced disease resistance and/or decreased time to death ( Goulson & Cory, 1995;Reilly & Hajek, 2008 ). However, Brown et al (2003) found no effect of host-resource stress on infection or immunity in bumblebees.…”
mentioning
confidence: 89%
“…There has been some theoretical examination of the effect of within generation DDP on host-parasite population dynamics. White & Wilson [52] use a discrete-time model, representing non-overlapping insect generations and found that DDP stabilizes the dynamics, while Reilly & Hajek [53] using a continuous-time model within the season and a discrete-time map between seasons reported that DDP has a destabilizing effect on the population. Given the intrinsic delays involved in maternal effects, the population dynamical implications are likely to be even more complex.…”
Section: Maternal Resources and Immunity M Boots And K E Roberts 4011mentioning
confidence: 99%